The Hindrance of Divorce due to Singer Avoidance in Dayak Muslim Society - Abdul Khair; Muhammad Norhadi; Rabiatul Adawiyah; Zainatul Fatmah (El-Mashlahah, 2026)
For the Dayak Muslim community, marriage agreements attempt to minimize divorce by imposing singers. However, for those experiencing marital problems but unable to pay singers, they might not divorce even after long periods of separation. This condition creates legal uncertainty. The study aimed to analyze the hindrances of divorce due to the singer's avoidance in the Dayak Muslim community. The research was empirical legal research in Gunung Mas Regency. Moreover, it used a juridical-sociological and socio-legal approach. Primary data were validated using triangulation techniques and analyzed in the context of relevant theory. The findings indicated that the application of singers in Dayak customary marriage agreements is formalistic, imposing sanctions for those who file for divorce without considering the fault of either party. This condition creates legal uncertainty because couples tend to live apart without a formal divorce due to the economic burden of customary sanctions. Therefore, rechtsvinding by customary authorities is needed through a more substantive approach to determining responsibility based on fault.